Acute effects of two different static stretching protocols on performance parameters in professional ballet dancer - Kotsala, E.; Panidi, I.; Bogdanis, G. C.; Androulidaki, A.; Giannakopoulou, G.; Koutsouba, M.; Donti, O. (Proceedings, 2019)
AIM: Ballet dancers` performance is based on the execution of complex technical skills that require an unusually large range of motion (ROM) and increased muscular power. Static stretching is commonly used to increase ROM, but it may induce a transient decrease in muscle power. However, this may depend on the population and stretching protocol. The purpose of this study was to compare the acute effect of a short (20 s) vs. a long (60 s) static stretching protocol on joint ROM and jumping performance in ballet dancers. MATERIAL & METHOD: Sixteen female professional ballet dancers (age, 25.9 ± 2.7; dancing experience, 19.6 ± 3.8 y) performed 5 days of testing using a single-leg stretching and jumping design. Baseline measurements of one-leg countermovement jump (CMJ) and a ballet technical jump with one leg ("temps levé", TL) were performed on the first visit. On the other four visits, dancers stretched their hamstrings, quadriceps and plantar flexors for 20 or 60 s per muscle group and then performed a CMJ or a TL in a counterbalanced order. This combination of stretching and jumping resulted in four conditions: long stretch-CMJ, long stretch-TL, short stretch-CMJ and short stretch-TL. In all conditions, ankle joint ROM was measured at rest and immediately after stretching. RESULTS: ROM significantly increased following stretching (p = 0.01) with no difference between stretching protocols (p = 0.505). CMJ height decreased post-stretching following both stretching protocols (p = 0.01); however, the long-duration static stretching induced a larger decrease in jump height (p = 0.020). TL height remained unchanged after the short and the long stretching protocols (7.7 ± 2.1 to 7.4 ± 2.2 vs. 7.7 ± 2.1 to 7.2 ± 2.0 cm, respectively, p = 0.701). CONCLUSION: Both stretching protocols similarly increased ankle joint ROM and decreased one-leg CMJ height immediately post-stretching. Also, both stretching protocols did not decrease TL height, probably because dancers are able to compensate for the stretch-induced deficit in muscle power through motor coordination. Keywords: flexibility; range of motion; jumping performance; technique; dance